Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 129710 by SOMEDAVONG last updated on 18/Jan/21

I=∫_0 ^(π/2) ((2304cosx)/((cos4x−8cos2x+15)^2 ))dx

I=0π22304cosx(cos4x8cos2x+15)2dx

Answered by MJS_new last updated on 18/Jan/21

2304∫((cos x)/((cos 4x −8cos 2x +15)^2 ))dx=       [t=sin x → dx=(dt/(cos x))]  =36∫(dt/((t^2 −t+1)^2 (t^2 +t+1)^2 ))=       [Ostrogradski′s Method]  =−((6t(t−1)(t+1))/((t^2 −t+1)(t^2 +t+1)))−6∫((t^2 −5)/((t^2 −t+1)(t^2 +t+1)))dt  −6∫((t^2 −5)/((t^2 −t+1)(t^2 +t+1)))dt=  =−3∫((6t−5)/(t^2 −t+1))dt+3∫((6t+5)/(t^2 +t+1))dt=  =6∫(dt/(t^2 −t+1))−9∫((2t−1)/(t^2 −t+1))dt+6∫(dt/(t^2 +t+1))+9∫((2t+1)/(t^2 +t+1))dt=  =4(√3)arctan (((√3)(2t−1))/3) −9ln (t^2 −t+1) +4(√3)arctan (((√3)(2t+1))/3) +9ln (t^2 +t+1)  ⇒ we have  2304∫_0 ^(π/2) ((cos x)/((cos 4x −8cos 2x +15)^2 ))dx=  [−((6t(t−1)(t+1))/((t^2 −t+1)(t^2 +t+1)))+4(√3)(arctan (((√3)(2t−1))/3) +arctan (((√3)(2t+1))/3))+9ln ((t^2 +t+1)/(t^2 −t+1))]_0 ^1 =  =2π(√3)+9ln 3

2304cosx(cos4x8cos2x+15)2dx=[t=sinxdx=dtcosx]=36dt(t2t+1)2(t2+t+1)2=[OstrogradskisMethod]=6t(t1)(t+1)(t2t+1)(t2+t+1)6t25(t2t+1)(t2+t+1)dt6t25(t2t+1)(t2+t+1)dt==36t5t2t+1dt+36t+5t2+t+1dt==6dtt2t+192t1t2t+1dt+6dtt2+t+1+92t+1t2+t+1dt==43arctan3(2t1)39ln(t2t+1)+43arctan3(2t+1)3+9ln(t2+t+1)wehave2304π/20cosx(cos4x8cos2x+15)2dx=[6t(t1)(t+1)(t2t+1)(t2+t+1)+43(arctan3(2t1)3+arctan3(2t+1)3)+9lnt2+t+1t2t+1]01==2π3+9ln3

Terms of Service

Privacy Policy

Contact: info@tinkutara.com